Exponential Stability of Linear Discrete Systems with Multiple Delays. (1st August 2018) - Baštinec, J.; Demchenko, H.; Diblík, J.; Khusainov, D. Ya.
Abstract : The paper investigates the exponential stability and exponential estimate of the norms of solutions to a linear system of difference equations with multiple delaysx k + 1 = A x k + ∑ i = 1 s B i x k - m i, k = 0, 1, …, wheres ∈ N, A andB i are square matrices, andm i ∈ N . New criterion for exponential stability is proved by the Lyapunov method. An estimate of the norm of solutions is given as well and relations to the well-known results are discussed.